On the Existence of Non-Zero Linear Continuous Functionals on Fréchet Spaces - Ng, Shu-Bun (My University, 1968)
This thesis is concerned with a necessary and sufficient condition for the existence of non-zero linear continuous functionals on Fréchet or more general topological vector spaces. The main idea is based on the famous Hahn-Banach theorem. Since the connection between Hahn-Banach theorem and separation theorems is well known, here we study some separation theorems as well.
Keywords: existence, non-zero, linear, continuous, functionals, Fréchet spaces, separation